German Unification and the Political Order – Thirty Years Later - Jürgen Kocka (Korea Europe Review: an interdisciplinary journal of politics, society, and economics, 2021)
The history of the post-war division of Germany marks an important point of reference for inter-Korean politics. Both, South Korean president Roh Tae-woo's Nordpolitik starting in 1988 and South Korean president Kim Dae-jung's Sunshine Policy (The Reconciliation and Cooperation Policy Towards the North) of 1998 seem to have been directly inspired by West German Chancellor Willy Brandt's so-called Neue Ostpolitik (New Eastern Policy) based on Egon Bahr's concept of Wandel durch Annäherung (change through rapproachment), an early and perhaps decisive step in the de-escalation of the Cold War. Today, the peaceful transition of East Germany toward democracy and the subsequent German unification continue to provide a hopeful historical example that peace and reconciliation on the Korean peninsula may be attainable.
Keywords: 300; German unification; non-violent revolution; East Germany; collapse of communism in Eastern Europe; NATO; question of German sovereignty